Capturing "Extraordinary" Soft‐Assembled Charge‐Like Polypeptides as a Strategy for Nanocarrier Design. Issue 39 (23rd August 2017) - Duro‐Castano, Aroa; Nebot, Vicent J.; Niño‐Pariente, Amaya; Armiñán, Ana; Arroyo‐Crespo, Juan J.; Paul, Alison; Feiner‐Gracia, Natalia; Albertazzi, Lorenzo; Vicent, María J.
Abstract: The rational design of nanomedicines is a challenging task given the complex architectures required for the construction of nanosized carriers with embedded therapeutic properties and the complex interface of these materials with the biological environment. Herein, an unexpected charge‐like attraction mechanism of self‐assembly for star‐shaped polyglutamates in nonsalty aqueous solutions is identified, which matches the ubiquitous "ordinary–extraordinary" phenomenon previously described by physicists. For the first time, a bottom‐up methodology for the stabilization of these nanosized soft‐assembled star‐shaped polyglutamates is also described, enabling the translation of theoretical research into nanomaterials with applicability within the drug‐delivery field. Covalent capture of these labile assemblies provides access to unprecedented architectures to be used as nanocarriers. The enhanced in vitro and in vivo properties of these novel nanoconstructs as drug‐delivery systems highlight the potential of this approach for tumor‐localized as well as lymphotropic delivery. Abstract : An "extraordinary" mechanism for charge‐like association enables self‐assembled anionic polypeptidic nanocarriers to be constructed. Covalent capture of these highly dynamic assemblies allows unprecedented architectures to be accessed. Their evaluation in relevant biological settings reveals a dramatically enhanced cell uptake, blood half‐life, and accumulation in lymph nodes, promising features for drug delivery in cancer treatment and immunotherapy.